The impact of monetary policy on inequality in the UK: An empirical analysis - Haroon Mumtaz; Angeliki Theophilopoulou (Queen Mary University of London, School of Economics and Finance, 2016)
The UK has experienced a dramatic increase in earnings and income inequality over the past four decades. We use detailed micro level information to construct quarterly historical measures of inequality from 1969 to 2012. We investigate whether monetary policy shocks played a role in explaining this increase in inequality. We find that contractionary monetary policy shocks lead to a deterioration in earnings, income and consumption inequality and contribute to their fluctuation. The response of income and consumption at different quantiles suggests that contractionary policy has a larger negative effect on low income households and those that consume the least when compared to those at the top of the distribution. Our evidence also suggests that the policy of quantitative easing contributed to the increase in inequality over the Great Recession.
Keywords: E2; E3; E4; E5; 330; Inequality; Earnings; Income; SVAR; Monetary policy shocks